Heat Stress Affects Pi-related Genes Expression and Inorganic Phosphate Deposition/Accumulation in Barley - Pacak, Andrzej; Barciszewska-Pacak, Maria; Swida-Barteczka, Aleksandra; Kruszka, Katarzyna; Sega, Pawel; Milanowska, Kaja; Jakobsen, Iver; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2016)
Phosphorus (P) in plants is taken from soil as an inorganic phosphate (Pi) and is one of the most important macroelements in growth and development. Plants actively react to Pi starvation by the induced expression of Pi transporters, MIR399, MIR827, and miR399 molecular sponge - IPS1 genes and by the decreased expression of the ubiquitin-conjugating enzyme E2 (PHOSPHATE2 - PHO2) and Pi sensing and transport SPX-MFS genes. The PHO2 protein is involved in the degradation of Pi transporters PHT1;1 (from soil to roots) and PHO1 (from roots to shoots). The decreased expression of PHO2 leads to Pi accumulation in shoots. In contrast, the pho1 mutant shows a decreased level of Pi concentration in shoots. Finally, Pi starvation leads to decreased Pi concentration in all plant tissues. Little is known about plant Pi homeostasis in other abiotic stress conditions. We found that, during the first hour of heat stress, Pi accumulated in barley shoots but not in the roots, and transcriptomic data analysis as well as RT-qPCR led us to propose an explanation for this phenomenon. Pi transport inhibition from soil to roots is balanced by lower Pi efflux from roots to shoots directed by the PHO1 transporter. In shoots, the PHO2 mRNA level is decreased, leading to an increased Pi level. We concluded that Pi homeostasis in barley during heat stress is maintained by dynamic changes in Pi-genes expression.